Optimalisasi Penggunaan Hasil Assesment untuk Tindak Lanjut Pembelajaran Pendidikan Agama Islam: Penelitian - Maulidani Ulfah; Remiswal; Khadijah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research discusses the importance of strategic steps to increase the effectiveness and quality of the learning process. In the context of modern education, assessment is not only seen as a tool for measuring learning outcomes, but also as a basis for making appropriate pedagogical decisions. This research aims to examine in depth how assessment results can be processed and utilized optimally by PAI teachers as a basis for designing follow-up learning that is adaptive, focused, and oriented towards increasing spiritual competence, religious attitudes, and students' understanding of the values ​​of Islamic teachings. The research method used is library research or what is usually called the library method. The library method is a research method that focuses on collecting, processing, analyzing and interpreting data from relevant literature or references. The research results show that the use of assessment and follow-up for PAI is not only assessed from a cognitive perspective, but also needs to be balanced from an affective and psychomotor perspective. The form of follow-up to the assessment is in the form of remedial for students who get a score less than the KKM, and enrichment is an effective form of increasing self-reflection for students to find out how deep their understanding is in a subject.